Functional dynamics to strengthen an agroecological technological innovation process in a developing country The case of plantain multiplication technology by Plants from Stem Fragments (PIF) in Cameroon - (:unkn) unknown (My University, 2023)
Source Agritrop Cirad (https://agritrop.cirad.fr/606072/) * Autres projets (id;sigle;titre): ;SERVInnov;(EU) Strengthening Innovation Support SERVices to enhance INNOVations for sustainable food production//
Keywords: African Research